A Longitudinal control for an autonomous vehicle using modified particle swarm optimization method - Hadi Salih Elias , Ghaidaa (International Journal of Engineering and Technology, 2024)
The control system is a very important part of the efficiency and safety of autonomous vehicles. This paper proposes the use of Particle Swarm Optimization (PSO) and Modified PSO (MPSO) algorithms to optimize Proportional Integral Derivative (PID) controller coefficients for a longitudinal dynamics vehicle system. The objective is to enhance system performance, measured by metrics such as maximum Overshoot (OS), Steady-State Error (SSE), Settling Time (t_s) (2%), and Rise Time 〖(t〗_r). The MPSO algorithm, when combined with the PID controller, demonstrates a 2.5% improvement over the traditional PSO algorithm. The study contributes by showcasing the effectiveness of MPSO in fine-tuning PID controllers for superior control of longitudinal vehicle dynamics, as evidenced by the optimized response specifications.